Electromagnetic tracking in interstitial brachytherapy: A systematic review - Sauer, Birte Christina; Dürrbeck, Christopher; Bert, Christoph (Frontiers in Physics, 2022)
Brachytherapy is a well-established treatment option for different cancer types. One treatment option, namely temporary afterloading brachytherapy, utilizes an encapsulated radioactive source, which is guided through implanted applicators to pre-defined dwell positions, to deliver highly conformal and concentrated doses to the target volume. However, treatment errors and uncertainties might still occur. The treatment therefore requires a stringent verification on an individual patient level, particularly in the form of applicator reconstruction. Electromagnetic tracking (EMT) is a possible verification option whose application neither relies on direct line of sight nor does it increase the radiation exposure. However, its systematic clinical application is not yet realized. This review will separate the concept of treatment verification through the use of electromagnetic tracking into four focus groups and categorize the relevant papers within said groups. The four focus groups are geometric assessment, applicator reconstruction, patient-individual quality assurance and adaptive treatment planning. The reviewed papers can be mainly sorted into the focus groups of geometric assessment and applicator reconstruction underlining the potential of EMT as an asset for reconstruction and localization. A smaller group of papers can be associated with patient-individual quality assurance where the detection of implant variations such as swaps within the connector cohort or single catheter shifts take center stage. The final focus group, adaptive treatment planning, is sparsely represented, yet the feasibility of an adaptive treatment course can be derived. This review will close with a discussion of possible improvements and illustrate the path ahead to clinical implementation.